Aesthetics of Evil in Middle Ages: Beasts as Symbol of the Devil - Piñero Moral, Ricardo Isidoro (Religions, 2021)
Since the very origin of art, human beings have faced the challenge of the representation of Evil. Within the medieval Christian context, we may find many beings which have attempted to convey the power of the devil. Demonic beings, terrifying beasts, fallen angels or even Satan himself can be frequently found and appear in many forms. They can be seen in chapitols, stained glass windows, codices … Our aim is to evaluate different creatures, animals and monstruous hybrids, which represent the efficient presence of the devil. We base our evaluation on some bestiaries, natural history books and encyclopedias from the XII and the XIII century, like the Bestiaire from Philippe de Thaon, Pierre de Beauvais, Guillaume le Clerc, or the so-called Cambridge Bestiary as well as the one from Oxford, the Livres dou Tresor from Brunetto Latini, the Liber monstrorum de diversis generibus, L’image du Monde from Gossuin, the Bestiario moralizzato di Gubbio, and of course, the Physiologus. Natural beings acquire a supernatural dimension in bestiaries and in natural history books. We will present the reader with a satanic bestiary, a short selection of these evil-related beings. In this, we will distinguish between those beasts representing evil through their ability to deceive and those which are able to generate not only fear, but also death.